WORK INTRUCTION (WI) BELT CONVEYOR 26BC05 DENGAN METODE PENYAMBUNGAN DINGIN (COLD SPLICING) PT. SEMEN BATURAJA (PERSERO) Tbk - Zakiah, Siti; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The development of science and technology continues to increase rapidly, not to mention in the industrial sector, Indonesia has now entered the era of the Industrial Revolution 4.0, this has resulted in an increasing need for professional human resources to support the development process of the industrial world. Automation in industry is part of developments that are influenced by technology, such as a means of transportation due to the demands to increase productivity, reduce production costs, make production easier and also the need for optimization in order to increase work efficiency. One of the means of transportation used in the industrial world is a belt conveyor, one of which is intensively used in every branch of the industry as an industry engaged in the cement industry using a conveyor belt to carry and distribute solid materials such as coal, limestone, clay, and other materials. Belt conveyors are used in industry, usually to move material in the unit loading section. The choice of belt conveyor as a means of transportation is that the capacity handled is the distance of material transfer, the conditions of transportation whether it is vertical, horizontal, or size. The conveyor belt used is adjusted to the material being transported, while the requirements that must be met are that the conveyor belt does not absorb water. In determining the conveyor belt layer can be determined by the width of the conveyor belt used